Effectiveness of health education intervention among the school teachers regarding management of traumatic dental injury in Modinagar - Vaibhav Vashishtha; Ritu Gupta; Patthi Basavaraj; Ashish Singla; Ravneet Kaur Malhi; Venisha Pandita (Wolters Kluwer Medknow Publications, 2016)
Background: Tooth avulsion is one of the most serious dental emergencies in children often occurring in school or during play time in school, therefore, the knowledge and perception of schoolteachers regarding the appropriate measures to be taken immediately after tooth avulsion is crucial to good prognosis. Objective: To assess the knowledge and attitude regarding dental trauma and its management among primary school teachers of Modinagar (Uttar Pradesh) before and after oral health promotional intervention. Methodology: A questionnaire based interventional study was done in Modinagar among 248 school teachers and carried out in three phases. In the initial phase, a self-administered structured questionnaire was delivered directly to the respondents. Afterward, an informative 45-min lecture on dental trauma and its management was given during the second phase and in the third phase; a follow-up survey was done to assess the outcome. Statistical analysis was done using Chi-square test with statistical significance at 5%. Results: Insufficient knowledge regarding dental trauma and its management was seen in the preliminary phase, but significant improvement of 90% and above, was observed in follow-up phase after the interventional period (P < 0.0001). Conclusion: The school teacher's level of knowledge on the management of dental trauma appears to be inadequate. This study highlights the importance of the provision of oral health promotion in improving the knowledge regarding management of dental trauma.